2015
DOI: 10.5812/ircmj.28021
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue and Psychological Distress: A Case Study Among Shift Workers of an Iranian Petrochemical Plant, During 2013, in Bushehr

Abstract: Background:Shift work is a well-recognized occupational health hazard in both industrialized and industrially developing countries. Prolonged working time, day/night shift rotation, circadian rhythm and sleep disorders, family and social problems are the most important features of shift working, which have serious complications.Objectives:The present study evaluated the fatigue and psychological distress and their relationship among shift workers, in a petrochemical plant (Southern Pars gas field) in Southwest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 35 publications
0
21
0
1
Order By: Relevance
“…According to the authors' best knowledge, although some previous studies investigated health-related factors among the employees of petrochemical companies (21,22), no research is conducted to measure the effectiveness of a tailored educational program to correct healthy nutritional behaviors and control CVD among the employees of a giant industrial company, using TPB model. Some studies have reported the effects of TPBeducational models on health behaviors, however, their impacts on metabolic status and risk factors of CVD are not investigated yet.…”
Section: Introductionmentioning
confidence: 99%
“…According to the authors' best knowledge, although some previous studies investigated health-related factors among the employees of petrochemical companies (21,22), no research is conducted to measure the effectiveness of a tailored educational program to correct healthy nutritional behaviors and control CVD among the employees of a giant industrial company, using TPB model. Some studies have reported the effects of TPBeducational models on health behaviors, however, their impacts on metabolic status and risk factors of CVD are not investigated yet.…”
Section: Introductionmentioning
confidence: 99%
“…1 Evidence suggest that a high percentage of employees in both developed and developing countries are exposed to psychosocial stressors at their work environment, with the consequences of exposure to such stressors are believed to be very substantial for employees, work places, and society. 1-4 Some of these consequences are cardiovascular diseases, musculoskeletal symptoms, mental problems, depression, stress, increased sickness absence and labor turnover, and decreased reduced quality of life, motivation and work productivity. 5-8 , Therefore, a better understanding on the work-related psychosocial factors may have a significant impact on safety and health promotion at work and on productivity enhancement, as well.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that shift work system has some adverse effects on health and work-life harmony of the employees. Reduced job satisfaction, fatigue, reduced alertness, daytime sleepiness and diminished job performance are the common shift work consequences (19)(20)(21). Besides decreased physical and mental health, uneven work schedules may result in social disorder and familial conflicts (19).…”
Section: Introductionmentioning
confidence: 99%